Occupational and paraoccupational diseases of the locomotor system in dentists - Piątkowska, Anna; Szymańska, Jolanta (Polish Journal of Public Health, 2009)
The work of a dentist is related to exposure to a number of burdensome and harmful factors that constitute a potential health threat. The commonest hazards include: locomotor system overload, exposure to infections and allergies, and the risk of sight and hearing damage. The problem of occupational hazards resulting from the work of a dentist concerns a population of over 12,000 practitioners. The most frequent complaint in dentists are spinal pain syndromes, as well as diseases of the musculoskeletal and peripheral nervous systems. Humeral epicondylitis and the carpal tunnel syndrome are recognized as occupational diseases related to the locomotor system; spinal pain syndromes, however, are considered paraoccupational diseases, where work conditions are one of many possible factors making the disease manifest. The musculoskeletal system overload in the dentist’s workplace should be minimized by adopting a variety of measures. Firstly, dentistry students should be taught ergonomics and occupational diseases prophylactics, and form correct working habits, while active practitioners should develop their skills in this area by participating in postgraduate training. Secondly, the dentist’s workplace should be properly designed and equipped according to the principles of modern ergonomics, while ergonomic work procedures, i.e. four-handed dentistry with horizontallypositioned patients, should be adopted; work organization should include rational time management. Thirdly, dentists should do simple physical exercises during work breaks and participate in various forms of physical activity in their free time. Fourthly, periodic prophylactic examinations of dentists should be adjusted to the specificity of their work and oriented towards early diagnosis of locomotor system overload, produce a detailed documentation and result in a systematic, periodic rehabilitation of the dentist’s musculoskeletal system.